Magnetic Nanoparticles - Katz, Evgeny (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The present book covers all research areas related to magnetic nanoparticles, magnetic nanorods, and other magnetic nanospecies, their preparation, characterization, and various applications, specifically emphasizing biomedical applications. The chapters written by the leading experts cover different subareas of the science and technology related to various magnetic nanospecies-providing broad coverage of this multifaceted area and its applications. The different topics addressed in this book will be of great interest to the interdisciplinary community active in the area of nanoscience and nanotechnology. It is hoped that this collection and its various chapters will be important and beneficial for researchers and students working in various areas related to bionanotechnology, materials science, biosensor applications, medicine, and many others. Furthermore, this book is aimed at attracting young scientists and introducing them to this field, in addition to providing newcomers with an enormous collection of literature references.